Pemberdayaan Guru Gugus Gajah Mada Bandar Kabupatem Batang Dalam Implementasi Aplikasi Cegah Kekerasan Seksual Berbasis Kearifan Lokal (CEKSALOKA) : Penelitian - Senowarsito; Yuli Kurniati Werdiningsih; Bambang Agus Herlambang (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Cases of sexual violence against children occurred successively in Batang Regency, including Bandar District. The incidence of this case is considered quite high, reaching 17 victims. Therefore, Empowering Community Partnership (PKM) program is urgent to be implemented immediately. This program is an activity carried out to improve social conditions in the target area. The aim of PKM is to implement the Local Wisdom-Based Sexual Violence Prevention Application (CEKSALOKA) at the schools in the area of KKG (Teacher Working Group) of Gugus Gajah Mada in Batang Regency in order to create an environment free of sexual violence against children. PKM partners are all schools and teachers at the KKG Gugus Gajah Mada in Bandar District, Batang Regency, which consists of 8 Public Elementary Schools in the neighborhood.